An Examination of Push and Pull Motivation of tourist Visit Tourist Attraction in Lembang - Silvie Adriani Merdekawati; Lusianus Kusdhibyo (Prosiding Industrial Research Workshop and National Seminar, 2018)
This study aims to identify the travel motivation of tourists visiting tourist attractions in Lembang. Motivation is a basic of tourists travel that is influenced by the push and pull motivation. The push motivation is a factor that comes from within the tourists, while the pull motivation comes from the characteristics of the destination. The method used is non-probability sampling. Used also accidental sampling. The questionnaires were distributed to tourists who are visiting tourism attraction in Lembang. A total of 333 respondents were used for further analysis. An exploratory factor analysis was carried out to identify new factors of push and pull motivation. The results show that there are four new factors of push motivation and three new factors of pull motivation of tourists visited Lembang. This result suggests that local tourism authority should consider the motivation factors to attract more tourists visit to Lembang.